Distribution of heavy metals and Pb isotopes in overbank sediments from the Amapari river, Pedra Branca do Amapari – Porto Grande, Amapá, Brazil - Silva, Danúbia Tavares da; Lafon, Jean Michel; Corrêa, José Augusto Martins (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
This work presents mineralogical, geochemical and Pb isotope compositions of heavy metals from overbank sediments of the Amapari river and its tributaries, in the region of Serra do Navio, central Amapá. The sediments are mainly composed of quartz, kaolinite, gibbsite and muscovite, displaying a large geochemical and Pb isotopic heterogeneity. The geochemical results indicate high contents of heavy metals and that the sediments underwent the same processes of enrichment for all investigated metals. The metals are mainly associated to fe-minerals, while clay minerals are not relevant for the concentration of those metals. The variation of Pb isotopic compositions permitted to define an isochron in the 207Pb/204Pb vs. 206Pb/204Pb diagram with an age of 2169 ± 140 Ma, indicating that the sediments came essentially from the surrounding Paleoproterozoic units (supracrustal rocks and associated granitoids), without any significant contribution from the units of the Archean basement. Metal contents and sample locations do not show any relationships with the major mining prospects in the area.